ANALISIS PERAN PERSONAL PROTECTIVE EQUIPMENT DALAM MENINGKATKAN KESELAMATAN JIWA AWAK KAPAL DI MV. HL ESPERANCE - Yabes Satgas; Endang Lestari; Ade Chandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Personal Protective Equipment (PPE) is one of the essential components in implementing occupational safety on board ships. However, the availability of PPE does not always guarantee that it will be used properly by crew members. This study aims to analyze the role of Personal Protective Equipment (PPE), particularly safety harnesses, in improving the safety of crew members on board MV. HL Esperance and to identify the factors influencing its implementation. This study employed a descriptive qualitative approach. Data were collected through direct observation during the sea practice program (PRALA), in-depth interviews with the Chief Officer as the primary informant and the Bosun as the supporting informant, as well as documentation. The data were analyzed using the Miles and Huberman interactive analysis model, which consists of data reduction, data presentation, and conclusion drawing. The findings indicate that PPE, particularly safety harnesses, plays a crucial role in minimizing the risk of occupational accidents during work at height and other high-risk operations. However, the implementation of PPE has not yet been optimal due to several factors, including low safety awareness, lack of work discipline, the perception that routine tasks are relatively safe, comfort-related issues, changing working conditions, and inconsistent supervision. Therefore, strengthening supervision, improving safety awareness, and fostering a strong safety culture are essential to optimize PPE implementation and minimize the risk of occupational accidents on board ships.